Plasma Ceramides and Sphingomyelins in Relation to Heart Failure Risk: The Cardiovascular Health Study. (July 2019) - Lemaitre, Rozenn N.; Jensen, Paul N.; Hoofnagle, Andrew; McKnight, Barbara; Fretts, Amanda M.; King, Irena B.; Siscovick, David S.; Psaty, Bruce M.; Heckbert, Susan R.; Mozaffarian, Dariush; Sotoodehnia, Nona
Abstract : Background: Ceramides exhibit multiple biological activities that may influence the pathophysiology of heart failure. These activities may be influenced by the saturated fatty acid carried by the ceramide (Cer). However, the associations of different circulating Cer species, and their sphingomyelin (SM) precursors, with heart failure have received limited attention. Methods and Results: We studied the associations of plasma Cer and SM species with incident heart failure in the Cardiovascular Health Study. We examined 8 species: Cer and SM with palmitic acid (Cer-16 and SM-16), species with arachidic acid (Cer-20 and SM-20), species with behenic acid (Cer-22 and SM-22), and species with lignoceric acid (Cer-24 and SM-24). During a median follow-up of 9.4 years, we identified 1179 cases of incident heart failure among 4249 study participants. In Cox regression analyses adjusted for risk factors, higher levels of Cer-16 and SM-16 were associated with higher risk of incident heart failure (hazard ratio for one SD increase:1.25 [95% CI, 1.16–1.36] and 1.28 [1.18–1.40], respectively). In contrast, higher levels of Cer-22 were associated with lower risk of heart failure in multivariable analyses further adjusted for Cer-16 (hazard ratio, 0.85 [0.78–0.92]); and higher levels of SM-20, SM-22 and SM-24 were associated with lower risk of heart failure in analyses further adjusted for SM-16 (hazard ratios, 0.83 [0.77–0.90], 0.81 [0.75–0.88], and 0.83 [0.77–0.90], respectively). No statistically significant interactions with age, sex, black race, body mass index, or baseline coronary heart disease were detected. Similar associations were observed for heart failure with preserved (n=529) or reduced (n=348) ejection fraction. Conclusions: This study shows associations of higher plasma levels of Cer-16 and SM-16 with increased risk of heart failure and higher levels of Cer-22, SM-20, SM-22, and SM-24 with decreased risk of heart failure. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00005133. Abstract : Supplemental Digital Content is available in the text.